(3eMOOGJ GdJShjb GdEdcJQhfj aj GdJYGedGJ GdJLGQjI hCKQgG Ydj GdYejd aj GdJTQjY GdebGQf (B/s - (3SYO eMeO SYO GdQLYGf GdeYhTQLjs; (3Ndjd ajcJhQ JGOQSs; (3LGeYI GdbGgQI(B.s (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B- (3LGeYI GdbGgQI,s, 2025)
(3aj WjGJ gPg GdQSGdI Sha jJe HMK hOQGSI GdJShjb GdGdcJQhfj hCKQg Ydi JLQHI GdeJYGedjf aj VhA GdJTQjYGJ GdebGQfI, hJMdjd cjajI JWHjb GdJShjb GdEdcJQhfj aj GdHjFGJ GdJLGQjI GdeNJdaI, Edi LGfH eYQaI JCKjQ Pdc Ydi Sdhc GdYedGA hJhLgGJge, EVGaI Edi GSJYQGV GdbhGfjf hGddhGFMGdeQJHWI HGdJShjb GdEdcJQhfj aj GdCfXeI GdOhdjI GdeNJdaI hebGQfJgG eY HYVgG GdHYV deYQaI GdahGQb hGdJTGHgGJ, HeG jDOj dJhVjM cjajI GdGSJaGOI ef gPg GdJTQjYGJ hJWhjQ GdMGdj efgG GdeRGefI GdJMOjKGJ GdeJSGQYI aj eLGdGJ GdJShjb GdEdcJQhfj HeG jVef MeGjI Mbhb heUGdM GdeJYGedjf hjMbb GdefaYI GdYGeI aj Xd KhQI GdGJUGd HGdbVGA GdSjHQGfjs
(3QSGFd fSNI efaQOIs
(3JMJhj Ydj UaMI YfhGf HGddZI GdCfLdjRjIs
(3CWQhMI (B((3OcJhQGI(B)- (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj, (B2025.s
(3HHdjhLQGajG(B: (3UaMGJ (B332-380s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJShjb GdEdcJQhfjs -- (3GdJTQjYGJ GdebGQfIs -- (3GdHjFGJ GdJLGQjI GdeNJdaIs -- (3Sdhc GdYedGA hJhLgGJges -- (3GdbhGfjf hGddhGFM GdeQJHWI HGdJShjb GdEdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs